Too much right can make a wrong: Setting the stage for the financial crisis - Richard J. Rosen (Federal Reserve Bank of Chicago, 2009)
The financial crisis that started in 2007 exposed a number of flaws in the financial system. Many of these flaws were associated with financial instruments that were issued by the shadow banking system, especially securitized assets. The volume and complexity of securitized assets grew rapidly during runup to the financial crisis that began in 2007. The paper discusses how the financial crisis can be viewed as a possible but logical outcome of a system where investors are overconfident, busy, and investing other peoples' money and intermediaries are set up to take advantage of investors' tendencies. The investor-intermediary risk cycle in this crisis is common to other crises. However, there are a number of factors that may have made the 2007 crisis more severe. Among them are the length of the pre-crisis period, the shift from financial intermediaries to the shadow banking system, the increasing interconnectedness among financial firms, and the increased leverage at some financial firms.
Keywords: 330